Охрана капитальных выработок от влияния очистных работ - Басинский Ю. М. Юрий Михайлович; Водянов В. Ф. Владимир Федорович; Кулешов В. М. Виктор Михайлович; Пиховкин В. С.; Кулешов В.М. Виктор Михайлович (Киев, Технiка, 1983)
Авт. указаны в вып. дан.